Trends Analysis of CPI in Indonesia, BPK Findings IC Weaknesses, and Disobedience with Laws - Wijaya, R. Muh. Syah Arief Atmaja (Journal of Economics, Business, and Government Challenges, 2023)
This study aims to reveal trends in BPK findings on the weaknesses of the internal control system and disobedience with laws also perceptions of corruption in Indonesia. This research was conducted by observing the Summary of Semester Examination Results (IHPS) published by the Supreme Audit Agency of the Republic of Indonesia (BPK RI) both in semester 1 and semester 2 from 2013 to 2022 and the Corruption Perceptions Index obtained from the BPK website, namely https://e-ppid.bpk.go.id/ and data on the Corruption Perceptions Index for Indonesia from 2013 to 2022 obtained from https://www.transparency.org/en/cpi / 2022 issued by Transparency International. The results of observations can be concluded that the problem of Disobedience with Laws in Indonesia has a significant impact on efforts to eradicate corruption. CPI shows that the response to corruption practices in Indonesia is still slow, and support from stakeholders is still minimal. In addition, the findings of SPI weaknesses and Disobedience with laws in the management of state finances also indicate challenges in increasing the effectiveness and efficiency of the use of public funds. So it is hoped that the better the governance of state finances, the higher the public's trust in the government and the better the development and welfare of the people as a whole